(untitled) (Raparin Journal of Humanities (RJH), 2025)
• The effect of a teaching strategy based on realistic assessment of communication and the method used on some learning Basic handball skills. • The differences between the teaching strategy based on realistic communication assessment and the method used in the post-test on some learning Basic handball skills. The researcher used the experimental method, and the research sample consisted of students in the institute of Physical Education at Koya city. They were divided into two groups: an experimental group that used teaching based on realistic evaluation using a communication method, and the control group used the established method. The research tools included some tests. Skill tests were carried out by hand. Homogeneity and equivalence were carried out in the research variables, and the validity and stability of the skill tests were ensured. After completing the experiment and applying post-tests, a set of conclusions were reached, the most important of which are: - • The teaching strategy based on realistic assessment in a communication style contributed to learning the basic handball skills identified in the research with a large degree of effect. • The effect size of the teaching strategy based on realistic assessment using the communication method was significantly better compared to the method used in all basic skills identified in the research. The study recommended emphasizing the use of a teaching strategy based on realistic assessment in a communication style as it is better than the method used in learning basic handball skills.